The Gender Based Development of Thailand - Lufer, Julie (My University, 1994)
This thesis explores the direct and causal link between the exploitation of women as a source of unpaid or cheap labour, and the rapid economic growth of the economies we consider newly industrialized. Thailand has been chosen as the case study because it serves to exemplify the kinds of effects gender based development has upon women. The hypothesis that was tested is that the exploitation of women - for example as unpaid labour in the home or the agricultural sector, or as a source of cheap waged labour in hotels or factories - is a necessary condition for the accelerated economic growth of Thailand.
The first chapter deals with feminist theory concerning patriarchal-capitalist relations. With heavy emphasis on the structuralist argument of such feminist theorists as Mies, Lim, Enloe, Hartman, Harstock and Lewenhak, the connections between capitalist economic arrangements and the underlying, hidden overtones of patriarchy are explored at length. The current condition of women in western as well as Thai society is related to the structure of capitalistpatriarchy and the process of housewifization.
In the second section of the first chapter, the historical aspects of women's work is related to the current economic context. It is demonstrated that clear linkages exist between the type of work women do in the home and the pay they receive in the capitalist workplace. It is hypothesized that because women's work was traditionally relegated to the private sphere that it has been undervalued, and thus, considered less economically viable.
Chapter two examines the historical development of Thailand. This section is divided into several phases beginning with the 1950s and proceeding into the contemporary stage. It is established that Thai development was, and currently is, significantly oriented towards production for export. These include the manufacturing sector, such as electronics, textiles and agricultural production. By nature, economies that have such heavy orientation on export are reliant on the cheap labour of its populace. In the case of Thailand, this includes predominantly women.
The third chapter explores specifically the sex selective migration patterns of Thailand and its relation to women's employment in the agrricultural sector. It was found that it is primarily young, unmarried women, ages 15-25 that are leaving rural areas of Thailand for Bangkok in order to earn a living. The kinds of changes that are occurring in agricultural production - for example, the mechanization of earn a living. The kinds of changes that are occurring in agricultural production - for example, the mechanization of farming - are seen as having a direct effect on young women's abilities to find employment in rural areas. It is demonstrated that with the advance of technology in the rural areas of Thailand, the social status of women has been affected in both positively and negatively. On the one hand, women's status in terms of decisions making patterns has improved. On the other hand, the traditionally high value ascribed to women vis a vis their reproductive abilities has diminished significantly. For instance, women are no longer viewed as the reproducers of the next generation of labour power. As such, men are not required to live in the matrimonial house since the religious conventions surrounding marriage and family have been relaxed.
Chapter four deals extensively with gender and Thailand's industrial sector, primarily the electronics, garment, and textile industries. It is established that Thailand's ability to attract offshore multinational investment is highly contingent upon it being able to provide semi-skilled, cheap labour. Thai women represent just such source of cheap labour. Most of the multinationals operating in Thailand are from either Japan, other South Asian countries, or the United States. Women's employment statistics in these industries are staggering. They comprise ln the electronics industry. The link between gender and development is probably no more evident than it is in these two economic sectors.
The second aspect of chapter four conceritrates on the informal sector of the Thai economy. This sector, unlike any other, is reliant upon the exploitation of women, especially young, uneducated women. The links between the tourism industry in Thailand and prostitution as a form of income generating activity are made very obvious. There are over 2 000 000 prostitutes in all of Thailand, 800 000 of whom are young women under the age of sixteen. The relationship between Thailand's needs for foreign currency and the high rate of prostitution associated with tourism are further illuminated.
It is concluded that indeed Thailand's development is highly contingent on the exploitation of women as a source of unpaid or cheap-waged labour. The most profitable sectors of the Thai economy tend to rely significantly on the labour of women. Women are, thus, indisputably the cornerstone of Thailand's economic growth. Yet, Thai women are disadvantaged in almost every aspect of their lives. They receive less education, have higher rates of illiteracy, receive lower wages, lack access to many occupations and are virtually invisible in Thai political life. Thai women have, as it was initially hypothesized, been profoundly affected by the gender based development of their country.
[missing page 29]
Keywords: Political Science; Political Science